(3efXhe GdOQQs - (3CMeO Hf Ydj Hf eMeO Hf MLQ GdTGaYj GdcfGfj GdYSbdGfj, TgGH GdOjf CHh GdaVd, GHf MLQ, J (B852 (3g` s; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg Ydi EMSGfg abO SFdJ ZjQ eQI Cf CLQO ef efXhei efJNHkG s
(3BNQgG (B:s
(3Ef WGH YjTi HCQV CbeJ ajgG edjG Je OjhGf GHf MLQ GdYSbdGfi , GdeSei HefXhe GdOQQ s
(3GfJNHg ef OjhGfg GdcHjQ hQJHg Ydi SHYI CfhGYs
(3GfXQ ai CjVkG GdCQbGe (B1239 - 241 - 1408 - 1412 (3COHs
(3hGdfSNI ajgG VHWs
(3HgG fXGe GdJYbjHI s
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
Keywords: (3GdCOHs